Relasi Interfirm-Control dalam Konfigurasi Strategi Jejaring Produksi Global pada Industri Teh (Studi Kasus Unilever dan PT. Perkebunan Nusantara VIII) - Dewi Setiyaningsih (Universitas 17 Agustus 1945 Jakarta, 2022)
This reseacrh aims at analyzing the involvement of Indonesia tea industry in the global production network using Dynamic Competitive concept which developed by Global Production Network theory 2.0. It takes Unilever Global as the leadfirm actor and PT.PN VIII as the suppliers There are three aspects which measure in dinamic competitive, there are cost-capability ratio, market development and financial discipline. From the analysis of the dynamic competitive of the leadfirm and suppliers, it shows that the configuration strategy of global production network builds between Unilever Global and PT.PN VIII is interfirm-control. This interfirm-control configuration makes Indonesia tea industry has less control in price decision and production rule.